Profile and Geospatial Analysis of Dog Bite Cases Attending the Antirabies Vaccine Outpatient Department at the Tertiary Level Hospital of Mumbai - Dinesh Asokan; Anjali Mall; Lalit Sankhe; Nagaraj Jaganathasamy; Geeta Pardeshi (Indian Journal of Public Health)
Background: Dog bites pose a significant public health concern in India, necessitating an understanding of their epidemiological profile and spatial distribution. Adopting the One Health approach, which considers the interconnection of human, animal, and environmental health, is vital for developing effective interventions. Objectives: The study aimed to assess the epidemiological profile and geospatial trends of dog bite cases in an urban area, focusing on the age and gender distribution of victims, severity of bites, and spatial distribution of cases to inform prevention strategies. Materials and Methods: A retrospective secondary data analysis was conducted on dog bite cases reported in 2022 at a tertiary care hospital in Mumbai. The epidemiological profile, including age, gender, and severity of bites, was examined. Quantum Geographic Information System (QGIS) was utilized for spatial distribution analysis, identifying hotspots within the urban area. Results: Of the 3350 cases, 70.7% were below 40 years old, 81.6% were male, and 78.18% had Category III bites indicating severe injuries. Most cases (74%) were caused by stray dogs. QGIS analysis revealed five hotspots within the urban area. Conclusion: The study highlights the predominance of dog bites among younger males and the severity of injuries. Spatial analysis identified specific hotspots, underscoring the need for targeted interventions. Implementing a comprehensive surveillance system incorporating GIS technology and adopting a One Health approach can enhance the control and prevention of dog bite cases and reduce the risk of rabies outbreaks.